EXTRATERRITORIALITY PRINCIPLE IN INVESTMENT DISPUTE SETTLEMENT UNDER ASEAN ENHANCED DISPUTE SETTLEMENT MECHANISM - Syariffudin Zaki, Muhammad Reza; Inggil, Kyle Pietra; Irawan, David Axel; Averine, Benedicta Nasya (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2023)
Trade and Investment are among the ways that are often used by modern countries today to become one of the main sources of state income. Indonesia as a destination country for trade and investment also has an important role in economic growth both domestically and in the ASEAN region. Indonesia is also one of the initiators of the Free Trade Area (FTA). In the spirit of realizing ASEAN as a trade and investment friendly zone, ASEAN launched a method called the ASEAN Protocol on Enhanced Dispute Settlement Mechanism (EDSM). This customized mechanism is in accordance with the spirit of ASEAN, namely The ASEAN way. Accordingly, the author took the initiative to conduct research related to the extraterritorial principle of the mechanism of Non-ASEAN countries that are geographically proximate to the ASEAN region. This research is entitled